Post-Cryo Survival of Rat Testicular Interstitial Cells in Hydroxyethyl Starch-Based Media - Pakhomov , Oleksandr (Problems of Cryobiology and Cryomedicine, 2021)
The development of cryoprotective serum-free or xeno-free media is required for safe use of cryopreserved testicular material for transplantation. In this study, the solutions containing 10% fetal bovine serum (FBS) or 5 mg/ml bovine serum albumin (BSA) did not significantly enhance the general survival of interstitial cells (ICs) after cryopreservation but increase their metabolic activity and steroid producing cell (HSD+-cells) survival. The use of 50 and 100 mg/ml hydroxyethyl starch (HES) in DMSO-based cryoprotective solutions instead of BSA or FBS enabled the improvement of the IC general survival and the survival of HSD+-cells. The use of HES supplemented media allowed to decrease the dimethyl sulfoxide (DMSO) concentration from 1.4 to 0.7 M and to preserve the amount and metabolic activity of ICs. Thus, designing cryoprotective media containing DMSO and HES can facilitate the formulation of serum-free solutions for cryopreservation that in turn paves a way for implementation of the use of cryopreserved material for practical medicine. Probl Cryobiol Cryomed 2021; 31(1): 070–081